Incorporating audio feedback to enhance inclusivity of courses - Sue Wilkinson (Association for Learning Development in Higher Education (ALDinHE), 2013)
Higher education institutions are under increasing pressure to provide inclusive courses that are accessible to all students, and with the percentage of disabled learners in HE increasing each year, this has become a key factor in institutional strategies and teaching and learning agendas.ÃÂ  This paper briefly highlights the issues that have risen to the need for alternative methods of feedback, and offers support for why audio feedback is one way of bridging the gap between learner engagement and tutor feedback.ÃÂ  Audio feedback is an alternative method of communicating advice to students that not only benefits disabled learners, but also non disabled learners and also tutors.ÃÂ ÃÂ